Acylation of cellulose nanocrystals with acids/trifluoroacetic anhydride and properties of films from esters of CNCs. (2nd January 2017) - Huang, Fengyuan; Wu, Xiaojie; Yu, Yan; Lu, Yanhua; Chen, Qifan
Highlights: ⿢ Esters of CNCs (ECNCs) were synthesized via long chain fatty acids and TFAA. ⿢ Films based on ECNCs were fabricated via casting/evaporation method. ⿢ ECNCs films preserve relative high tensile parameters after water absorbing. Abstract: To eliminate the effect of humidity on nanopapers from nanocellulose, esters of CNCs (ECNCs) were synthesized via acylation of cellulose nanocrystals (CNCs) with fatty acids and Trifluoroacetic anhydride (TFAA). The structure information of ECNCs was confirmed via FTIR, degree of substitution (DS) determination, and XRD, respectively. With the increase of DS, the ECNCs could be dissolved in dichloromethane, which provided a ready way for fabrication of ECNCs films via casting/evaporation method. The tensile property, transmittance, hydrophobicity, thermal property and oxygen permeability of films were tested with universal tensile tester, UV⿿vis spectrophotometer, Contact angle tester, Simultaneous thermal analyzer and Oxygen permeability tester, respectively. With the increase of DS, the contact angles of ECNCs increased, and the water uptake decreased. The enhancement of hydrophobicity promised the preservation of tensile parameters for films after water absorbing. The hydrophobicity, high transmittance, and high oxygen barrier property make films have potential application in packaging filed.